Endothelial dysfunction and thrombotic complications associated with SARS-CoV-2 in adults: a systematic review - Pamplona, Mariane Arakawa; Taveira, José Hittalo; da Mata, Karina Magalhães; Moraes, Kleber Silva; França, Maria Clara Mendonça; Ribeiro, Anna Beatriz de Assis; da Mata, Renata Alves; Fernandes, Cleverson Rodrigues (Brazilian Journal of Implantology and Health Sciences, 2023)
Introduction: During the pandemic, occurrences of thromboembolic complications and endothelial dysfunctions associated with COVID-19 were observed. Thus, the pathophysiology of the mechanisms of action are not fully elucidated. Methods: Aiming at a better understanding of the associated mechanisms of endothelial function due to COVID-19, a systematic review was developeded out using index databases and a selection process in which the inclusion criteria were articles that addressed the mechanism of thrombotic events by endothelium dysfunction and publications that associate COVID-19 with thrombotic complications in adults up to 59 years of age. Conclusion: SARS CoV 2 is associated with altered endothelial function by endothelial mechanisms induced by direct viral infection and injury, leading to changes in the angiotensin II/AT1 axis and inflammatory response.